The Effect of Buzz Wire Games On The Fine Motor Skills of Children With Phase B SLBN Cinta Asih - Faturohman, Ian; Sudrazat, Adang; Lengkana, Anggi Setia (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the effect of buzz-wire games in improving the fine motor skills of children with phase B SLBN Cinta Asih Soreang. Fine motor is one of the important aspects in the development of children's movement. One Group Pre-test Post-test Design research method to determine differences before and after being given certain treatments. The sample used in this study was the total sample technique which is where all phase F Tunagrahita children at SLBN Cinta Asih Soreang aged 7-12 years. Using fine motor skills test as an instrument in research. The results of the normality test data processing resulted in a significant pretest of 0.966 while the posttest was 0.880. From these data, it can be interpreted that the normality test is normally distributed, because the significance> 0.05. Then the homogeneity test carried out resulted in a significance of 0.899. From these data, it can be interpreted that the homogeneity test is homogeneous. Then the Paired Sample T-test was conducted to determine the effect produced with a value of 0.001. So, it can be said to influence because <0.05. The study found that fine motor skills (after using the application of the buzz-wire game training model) increased more than the initial test. This shows that the application of buzz wire games can improve fine motor skills in phase B Tunagrahita children at SLBN Cinta Asih Soreang.